MdDREB2A in apple is involved in the regulation of multiple abiotic stress responses - Xinyu Lian; Xinyu Zhao; Qiang Zhao; Guiluan Wang; Yuanyuan Li; Yujin Hao (Horticultural Plant Journal, 2021)
Abiotic stress has a serious effect on plant growth. The transcription factor DREB2A is a member of the AP2/ERF family, which is widely involved in abiotic stress response. However, the function of apple MdDREB2A has not been systematically investigated. In this study,MdDREB2A was isolated from the cultivar ‘Royal Gala’. The open reading frame of MdDREB2A was 1 197 bp in length and it encoded a protein of 398 amino acids with molecular weight of 43.8 kD. As a transcription factor, MdDREB2A was located in the nucleus. qRT-PCR analysis showed that MdDREB2A was involved in responses to drought, salt, and ABA stresses. Under these stress treatments, the relative electrical conductivity, superoxide anion and malondialdehyde (MDA) in transgenic materials significantly decreased, and the content of proline increased in MdDREB2A transgenic plants, compared to the controls, indicating that MdDREB2A transgenic apple calli and transgenic Arabidopsis exhibited improved resistance to abiotic stress. This study introduces a candidate gene for the genetic improvement of crop resistance and reveals important function of MdDREB2A in the regulation of abiotic stress response.